Yin Yang 1-stimulated long noncoding RNA bladder cancer-associated transcript 1 upregulation facilitates esophageal carcinoma progression via the microRNA-5590-3p/programmed cell death-ligand 1 pathway. Issue 4 (1st April 2022) - Cheng, Jingge; Yang, Qian; Han, Xia; Wang, Haotian; Wu, Kun; Zhao, Hongye
ABSTRACT: Esophageal carcinoma (EC) is a common gastrointestinal malignancy that poses a threat to public health worldwide. Long noncoding RNA (lncRNA) bladder cancer-associated transcript 1 (BLACAT1) exerts a tumorigenic role in several malignant tumors; nevertheless, its function in EC remains largely unknown. Besides, programmed cell death-ligand 1 (PD-L1), an oncogene in numerous human cancers, has been identified as a therapeutic target for EC. Therefore, we intended to explore the potential regulatory network involving BLACAT1 and PD-L1 in EC. In this study, we observed increased BLACAT1 and PD-L1 levels in EC tissues and EC cell lines. Moreover, YY1 could activate BLACAT1 transcription in EC cells (TE-1 and EC9706). In addition, in vitro and in vivo experiments demonstrated that BLACAT1 facilitated EC cell proliferation and metastasis and EC tumor growth. Also, the effects of BLACAT1 silencing on EC cell functions were partially reversed by PD-L1 overexpression. Besides, it was identified that BLACAT1 competed with PD-L1 to bind to miR-5590-3p in EC cells. Furthermore, miR-5590-3p suppression could abrogate the functional effects of BLACAT1 knockdown on EC cells; while PD-L1 silencing partly abolished the promoting effects of miR-5590-3p suppression on the biological functions of EC cells. To sum up, YY1-induced BLACAT1 accelerated EC progression via regulating the miR-5590-3p/PD-L1 axis. GRAPHICAL ABSTRACT: uf0001